(3bhGYO GdeWGQMIs - (3MSjf Hf HOQ Hf CjGR Hf YHO Gddg, CHh eMeO, LeGd GdOjf, GdHZOGOj,J (B681 (3g` s ((3CHhWGdH Hf EHQGgje GdLeGQfj GdeLGeQ s)
(3ChdgG (B:s
(3hHYO, ade jRd jYJdL aj UOQj, hjJQOO aj acQj, eY bdI HVGYJj ef GdYde s
(3BNQgG (B:s
(3bhd OYHd(B: (3eG CWjH GdYjT aCeG Ydi Cf dG CQi hLgc jhekG gPG BNQ eG JjSQ dj PcQg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdeYgO Hg fSNI CNQis
(3GfXQ GdLRA GdChd Qbe (B125 (3fMh HYfhGf GdbhGYO ai GdfMhs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3fSNI KGfjI s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs